Sandoz Headquarters - Office Complex Novartis, Rueil-Malmaison, 1962-1968, by Martin Burckhardt and Bernard-Henri Zehrfuss - Blasi, Ivan (Docomomo Journal, 2012)
Agnès Cailliau, Chair of docomomo France alerted docomomo International that the original Headquarters and Laboratories of Sandoz were going to be completely demolished. After writing letters to the Mayor of Rueil-Malmaison and to Novarti’s President, the pharmaceutical company answered that their previous Basel intervention was an example of their care for heritage, that the structure of the building in Rueil-Malmaison had not aged well and did not live up to the company’s standards and that the project of architect Patrick Berger was in line with their heritage policy.